Digital-Based Interactive Learning Transformation Optimization of Canva: A Case Study at SMPN 3 Padang - Salma, Admi (Fakultas MIPA Universitas Negeri Padang, 2025)
The implementation of digital-based interactive learning in the classroom has the potential to increase student engagement and motivation in the learning process. One of the main problems at SMP N 3 Padang is that teachers have varying levels of basic skills in creating technology-based interactive learning. As a result, digital learning cannot be implemented effectively in the classroom. Therefore, it is very important to improve teachers' skills in creating digital instructional media. Canva is one of the most user-friendly digital learning tools and is accessible to users with limited technical expertise. The study conducted at SMP 3 Padang aimed to address teachers' challenges by providing Canva optimization training. The objective of this study was to enhance teachers' ability to utilize Canva for creating digital-based interactive learning. The results show that teachers' ability to create interactive instructional media with Canva has significantly improved.